The Communication Patterns of Husband and Wife Couples in Resolving Household Conflicts: Islamic Family Law Perspectives - Syaflin Halim,; Syamsurizal,; Firdaus,; Desminar,; Jaffar, Mohammad Najib; Elma Rida Yanti, (KARSA Journal of Social and Islamic Culture, 2024)
Husband and wife have different characteristics and are difficult to reconcile; these differences in characteristics can lead to conflict in the household. One of the factors that causes conflict in the household is that communication is not going well. This research focuses on the communication patterns of husband and wife in resolving family conflicts from the perspective of Islamic family law. To answer this problem, research was carried out using the literature study method. The first step was identifying relevant library sources, including books, scientific journals, articles, theses and other publications. These sources are evaluated based on the content's reliability, legitimacy, and novelty. Next, the researcher synthesizes findings from various sources to draw comprehensive conclusions. The research results identify five key factors shaping communication patterns in Muslim marital relationships: integration of religious teachings, religious commitment, gender role expectations, cultural influences, and application of religious principles in conflict resolution, especially Shariah law. Integrating these elements is essential for fostering healthy commu-nication and strengthening marital bonds.